Enhancing State Asset Recovery Through Asset Confiscation: Evaluating the Legal Framework and Its Implementation in Indonesia's Anti-Corruption Regime - Ichwan Effendi; Donny Setha; Mospa Darma (International Journal For Advanced Research, 2026)
Corruption remained one of the most serious threats to good governance and sustainable development in Indonesia because it caused substantial state financial losses and undermined public trust in government institutions. Asset confiscation was recognized as an essential legal mechanism not only to punish offenders but also to recover assets derived from corruption and restore state financial losses. This study examined the legal framework governing asset confiscation, analyzed its implementation within Indonesia's criminal justice system, and evaluated its effectiveness in supporting state asset recovery. The study employed a normative legal research method using statutory, conceptual, and case approaches. Data were collected through a comprehensive review of legislation, judicial decisions, legal doctrines, and scholarly publications and were analyzed qualitatively using descriptive legal analysis. The findings indicated that Indonesia had established a comprehensive legal framework regulating asset confiscation through national legislation and international legal instruments. However, the implementation of asset confiscation remained constrained by practical challenges, including difficulties in tracing illicit assets, ownership disputes, lengthy execution procedures, cross-border asset transfers, and limited institutional coordination. These challenges reduced the effectiveness of recovering state financial losses despite the availability of adequate legal regulations. The study concluded that strengthening institutional coordination, improving asset-tracing mechanisms, accelerating execution procedures, and enhancing international cooperation were essential to optimizing asset recovery. Effective implementation of asset confiscation was therefore found to be a strategic instrument for strengthening anti-corruption law enforcement, improving legal certainty, promoting accountability, and protecting state financial interests.